2013
DOI: 10.1186/2036-7902-5-6
|View full text |Cite
|
Sign up to set email alerts
|

Integrated medical school ultrasound: development of an ultrasound vertical curriculum

Abstract: BackgroundPhysician-performed focused ultrasonography is a rapidly growing field with numerous clinical applications. Focused ultrasound is a clinically useful tool with relevant applications across most specialties. Ultrasound technology has outpaced the education, necessitating an early introduction to the technology within the medical education system. There are many challenges to integrating ultrasound into medical education including identifying appropriately trained faculty, access to adequate resources,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
186
0
5

Year Published

2014
2014
2020
2020

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 177 publications
(193 citation statements)
references
References 25 publications
2
186
0
5
Order By: Relevance
“…Some [5][6][7][8][9][10][11][12][13][14][15][16][17][18][19] Fifteen papers describe variously integrated ultrasound curricula. Five studies are notable for the numbers of medical students involved in a formal evaluative process (>150) [5][6][7][8][9].…”
Section: Learning Category-incorporation Of Ultrasound Into Teaching mentioning
confidence: 99%
“…Some [5][6][7][8][9][10][11][12][13][14][15][16][17][18][19] Fifteen papers describe variously integrated ultrasound curricula. Five studies are notable for the numbers of medical students involved in a formal evaluative process (>150) [5][6][7][8][9].…”
Section: Learning Category-incorporation Of Ultrasound Into Teaching mentioning
confidence: 99%
“…Since 2006, several more medical schools have similarly incorporated ultrasound education into the entire medical school curricula and studies have described these curricula as effective, feasible, and highly regarded by medical students [24,26,28,29]. In a review of University of South Carolina's integrated ultrasound curriculum, Hoppmann et al [24] demonstrated that over 90 % of students felt that the integration of ultrasound education in the medical school curriculum enhanced their understanding of the basic sciences in their preclinical education.…”
Section: History Of Ultrasound In Undergraduate Medical Educationmentioning
confidence: 99%
“…To date, physician education in diagnostic sonography was previously withheld until residency and varied widely between specialties. [25] Studies [26][27][28] showed that pre-clinical medical students can obtain a residentlevel understanding of ultrasonography given proper means and methods of training. Specifically in Tanzania, previous studies [24,29] have demonstrated the importance of ultrasound in low-resource settings and the success of training programs in rural Tanzanian hospitals and clinics.…”
Section: Discussionmentioning
confidence: 99%